KEY DRIVING FACTORS FOR TOURIST SATISFACTION AND REVISIT INTENTIONS IN NORTH SULAWESI - Vinlyvia Gloria Ribka Wulus; Deske W. Mandagi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The tourism sector is one of the economic cornerstones and an important source of economic drivers. This study aims to investigate the relationship between various tourism elements and their impact on tourist satisfaction and revisit intention in North Sulawesi, Indonesia. Utilizing a quantitative descriptive research design, the study employs a closed questionnaire to gather data from 206 respondents, selected through simple random sampling. The Structural Equation Model (SEM) is used to analyze the data and test the hypotheses. The results indicate that among the 5A's of tourism elements, Accommodations, Attractions, and Amenities significantly influence Tourist Satisfaction, Furthermore, Tourist Satisfaction has a significant effect on Revisit Intention. This study highlights the critical factors influencing tourist satisfaction and their subsequent effect on revisit intentions, offering valuable insights for tourism management and policymaking in North Sulawesi. The findings suggest that improving accommodations, attractions, and amenities could enhance overall tourist satisfaction and increase the likelihood of repeat visits.